2008
DOI: 10.1111/j.1365-2133.2008.08666.x
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the management of basal cell carcinoma

Abstract: Summary This article represents a planned regular updating of the previous British Association of Dermatologists guidelines for the management of basal cell carcinoma. These guidelines present evidence‐based guidance for treatment, with identification of the strength of evidence available at the time of preparation of the guidelines, and a brief overview of epidemiological aspects, diagnosis and investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
489
1
36

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 726 publications
(537 citation statements)
references
References 198 publications
(316 reference statements)
11
489
1
36
Order By: Relevance
“…The vast majority of patients in this study were farmers and rural residents, similar to what was reported in the literature concerning the environmental risk factors for developing NMSC (15,17). Associated with sun exposure, other risk factors may influence the onset of NMSC (1,2,8,9). In this series, there was a predominance of patients with phototypes I to III Fitzpatrick classes, consistent with the predominance of fair-skinned people in the study area due to the local colonization pattern (13).…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…The vast majority of patients in this study were farmers and rural residents, similar to what was reported in the literature concerning the environmental risk factors for developing NMSC (15,17). Associated with sun exposure, other risk factors may influence the onset of NMSC (1,2,8,9). In this series, there was a predominance of patients with phototypes I to III Fitzpatrick classes, consistent with the predominance of fair-skinned people in the study area due to the local colonization pattern (13).…”
Section: Discussionsupporting
confidence: 64%
“…Chronic sun exposure seems to be the main cause of SCC (1-3, 9, 15). In contrast, BCC occurs due to intermittent sunlight exposure (1)(2)(3)15) and history of sunburns (2), especially during childhood and adolescence (1,2,8). Most of the evaluated patients (18/25) reported exposure to UV radiation since childhood in a chronic form.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations